Lactate Dehydrogenase as A Potential Prognostic Biomarker in Subarachnoid Haemorrhage: A Systematic Review - Yang Yang Endro Arjuna; Alexander Erick Purnomo; Jeremiah Hilkiah Wijaya; Mary Christina Elsa; Yusak Mangara Tua Siahaan; Made Agus Mahendra Inggas; Randra Frits Christopher; Michelle Gloria Setiawan; Haddiyya Wardhani Nugroho (Lumina : Indonesian Journal of Neurology, 2025)
Background: Subarachnoid haemorrhage (SAH) lacks specific prognostic blood markers, but lactate dehydrogenase (LDH), linked to cellular damage, shows potential for predicting adverse outcomes in SAH patients. Elevated LDH levels may reflect anaerobic metabolism and tissue injury following SAH, providing insight into disease severity and complications. This review explores the relationship between lactate dehydrogenase levels and outcomes in SAH patients. Method: A systematic review was conducted using PubMed, Europe PMC, ScienceDirect, and Google Scholar, searching for terms like "Lactate Dehydrogenase," "LDH," "Subarachnoid Haemorrhage," and "Outcome" up to March 3, 2025. Studies comparing LDH levels with Modified Rankin Score (mRS) and secondary outcomes such as Hunt-Hess grade, Fisher grade, complications, and mortality were included. Result: Seven studies involving 5,985 participants met inclusion criteria. Higher LDH levels correlated with worse mRS scores, increased delayed cerebral ischemia (DCI), postoperative pneumonia, severe Hunt-Hess and Fisher grades, and higher mortality. Using the ROBINS-I tool, four studies showed low risk of bias, and three had moderate risk. Discussion: Elevated LDH levels predict adverse outcomes in SAH, highlighting its prognostic value. As a marker of cellular damage and anaerobic metabolism, LDH reflects tissue injury and hypoxia post-SAH, explaining its link to complications like delayed cerebral ischemia (DCI) and pneumonia. This physiological basis supports its role in risk stratification, aiding early identification of high-risk patients for targeted interventions and improved outcomes. Conclusion: Early measurement of LDH levels after SAH onset may help predict patient outcomes and complications, aiding clinical decision-making and improving patient management strategies.